Enantioselective Double Aldol Reactions Involving the Sequential Activation of Silicon Tetrachloride by Chiral Phosphine Oxides - Kotani, Shunsuke; Sugiura, Masaharu; Nakajima, Makoto (Synlett, 2014)
This account summarizes our recent studies on the development of phosphine oxide-catalyzed enantioselective double aldol reactions that extend hypervalent silicon chemistry by using a Lewis base catalyst. Chiral phosphine oxides repeatedly activate silicon tetrachloride and form hypervalent silicon complexes, thereby promoting sequential activation of substrates and realizing enantioselective double aldol reactions. The account describes several relevant applications of these reactions.1 Introduction2 General Concept of Sequential Catalysis by a Lewis Base2.1 Lewis Base Catalysis with Chlorosilanes2.2 Phosphine Oxides as Lewis Base Catalysts3 Branched-Type Double Aldol Reactions3.1 Enantioselective Branched-Type Double Aldol Reactions Catalyzed by Phosphine Oxides3.2 Mechanism of the Branched-Type Double Aldol Reactions3.3 Applications of the Branched-Type Double Aldol Reactions in Enantioselective Syntheses of 2,3-Dihydropyran-4-ones4 Linear-Type Double Aldol Reactions4.1 Enantioselective Linear-Type Double Aldol Reactions Catalyzed by Phosphine Oxides4.2 Mechanism of the Linear-Type Double Aldol Reactions4.3 Application of the Double Aldol Reactions to the Total Synthesis of (–)-Ericanone5 Conclusions
Keywords: aldol reaction; asymmetric catalysis; multicomponent reaction; silicon; phosphorus; tandem reaction